Respuesta :

Answer: 3rd, 4th, and 5th are correct.

Step-by-step explanation:

We know that the equation 6(t+2) can be simplified to 6*t+6*2, also 6t+12. This causes any statements saying a variable with a certain value applies to one side also applies to the other.

Answer:

- The value of both expressions when t = 3 is 30

- The value of both expressions when t = 7 is 54

- The expressions are equivalent

Step-by-step explanation:

Plug in each value of t into the expressions:

6t + 12, when t = 3 equals 30

6t + 12, when t = 7 equals 54

6(t + 2), when t = 3 equals 30

6(t + 2), when t = 7 equals 54

We have the same answers for both expressions, meaning they are equivalent.